Saudi Arabia, the Arab and Islamic World on the Eve of the Formation of the OIC - S V Kovalev (Vestnik RUDN. International Relations, 2013)
The article discusses the features of the socio-political situation in the regions of the spread of Islam on the eve of the establishing of the Organization of Islamic Conference, as well as the role of Saudi Arabia in the creation of this organization.